Autonomous driving and advanced driver-assistance systems (ADAS) : applications, development, legal issues, and testing - Joseph, Lentin; Mondal, Amit Kumar (Boca Raton : CRC Press, 2022)
"Autonomous Driving and Advanced Driver Assistance Systems (ADAS) outlines the latest research relating to autonomous cars and advanced driver-assistance systems, including the development, testing and verification for real-time situations of sensor fusion, sensor placement, control algorithms, computer vision, and more. With an infinite number of real-time possibilities that need to be addressed, the methods and examples included make this book a valuable source of information for academic and industrial researchers, automotive companies and suppliers"--
OCLC-licensed vendor bibliographic record.
Keywords: Automated vehicles; Driver assistance systems; COMPUTERS / Computer Graphics / Game Programming & Design; COMPUTERS / Machine Theory; COMPUTERS / Computer Engineering